MEANS OF ARTISTIC EXPRESSION IN POETRY, ISSUES OF ANALYSIS AND INTERPRETATION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis explores the primary means of artistic expression in poetry, such as diction, imagery, symbolism, tone, and structure, while addressing the interpretive challenges they present. Poetry’s inherently layered and ambiguous nature demands deep analysis that considers not just linguistic elements but also historical, cultural, and emotional contexts. Through examining various literary approaches and theoretical frameworks, the paper underscores the complexity of poetic interpretation and the balance between authorial intent and reader response. The study concludes that effective analysis of poetry requires both technical knowledge and a sensitivity to language’s expressive power.